STUDY OF NEGATIVE REFRACTIVE INDEX IN Rb FOUR-LEVEL N-TYPE ATOMIC GAS MEDIUM - Huy Bang Nguyen; Nguyen Mai Anh Le; Thi Minh Phuong Le; Hai Quang Ho; Van Doai Le (Tạp chí Khoa học Đại học Đà Lạt)
In this work, we study the generation of a negative refractive index based on electromagnetically induced transparency (EIT) in a Rb four-level N-type atomic gas medium. We derive analytic expressions for the relative permittivity and relative permeability of the medium according to the parameters of the probe, pump, and signal laser fields. We then investigate the variation of the real parts of the relative permittivity and relative permeability with respect to the intensity and frequency of the pump and signal laser fields. In the presence of the pump laser beam, the medium becomes transparent to the probe laser beam even in the resonant region. At the same time, the real parts of the relative permittivity and relative permeability are simultaneously negative (i.e., the medium exhibits a negative refractive index) in the EIT spectral domain. In the presence of the signal laser beam, the EIT effect occurs over two different frequency domains of the probe beam, so a negative refractive index is also generated in these two frequency domains. The investigation of the real parts of the relative permittivity and relative permeability with intensity and frequency of the pump and signal laser fields allowed us to find the laser parameters for the appearance of the negative refractive index, which can be useful for experimental observations.